Urgensi Sertifikasi Halal pada Coffee Shop di Indonesia - Nurjanah Nurjanah; Murniyetti Murniyetti; Wirdati Wirdati; Al Ikhlas (ISLAMIKA, 2022)
Law on Halal Product Guarantee in Indonesia which came into effect in October 2019 stipulates that products that are circulated, entered, and traded must be certified halal. The various types of coffee drinks currently circulating are very diverse and most of these products have not received a halal certificate. The research method used by the researcher is descriptive qualitative, namely through the data that has been obtained and collected. The result of this study is that awareness of halal-certified products for coffee shop business actors is still very low. Lack of knowledge about the non-alcoholic rum menu in coffee for which there is no halal information from MUI, therefore the importance of halal certification from MUI for this product so that it can be said to be halal. The conclusion of this study is that halal certification is a requirement to include a halal label on product packaging with the aim of providing certainty of halalness.